2011
DOI: 10.1016/j.fertnstert.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Ramifications of adolescent menstrual cycles ≥42 days in young adults

Abstract: Objective To determine to what degree annual reports from ages 14 to 19 years of menstrual cycles ≥42 days would be associated with increased body mass index (BMI), waist circumference, glucose, insulin, and homeostasis model assessment insulin resistance (HOMA-IR) at ages 14–25 years. Design Prospective 11-year follow-up from ages 14 to 25 years. Setting Urban-suburban schools, post–high school. Patient(s) A total of 370 schoolgirls. Intervention(s) None. Main Outcome Measure(s) BMI, waist, insulin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…This finding is at variance with the results of our study because the obese girls with hirsutism, despite their hyperandrogenism that correlated with their waist circumference, did not have a greater degree of obesity, higher plasma insulin levels or lower serum SHBG levels than the obese girls without hirsutism. In accordance with our findings, menstrual disorders in obese women have been associated with a high degree and early onset of obesity, centrally distributed body fat (12,14,43,47) and a high 30 min insulin peak in the OGTT (48). We found no significant differences in the serum androgen levels of the obese adolescent girls with a menstrual disorder than those without a menstrual disorder.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is at variance with the results of our study because the obese girls with hirsutism, despite their hyperandrogenism that correlated with their waist circumference, did not have a greater degree of obesity, higher plasma insulin levels or lower serum SHBG levels than the obese girls without hirsutism. In accordance with our findings, menstrual disorders in obese women have been associated with a high degree and early onset of obesity, centrally distributed body fat (12,14,43,47) and a high 30 min insulin peak in the OGTT (48). We found no significant differences in the serum androgen levels of the obese adolescent girls with a menstrual disorder than those without a menstrual disorder.…”
Section: Discussionsupporting
confidence: 92%
“…The first novel finding in our study was that menstrual cyclicity ≥42 days, associated with hyperandrogenism [36], ascertained yearly in post-menarchal girls from ages 14 through 19, was independently associated with increasing ApoB/ApoA1 ratios. In our study, 90% of girls were post-menarchal by age 14, the same as reported in the third NHANES study [37] where 90% of US girls were menstruating by 13.75 years.…”
Section: Discussionmentioning
confidence: 96%
“…There was no association ( p = 0.96) between age at menarche and the number of annual reports of menstrual cycles ≥42 days from ages 14 to 19. In our current and recent [21, 22] studies of the relationships of delayed cyclicity to CVD risk, metabolic syndrome, obesity, and polycystic ovary syndrome (PCOS), annual reports of menstrual cycles ≥42 days from ages 14 to 19 were used to identify girls with unequivocal menstrual delay. The ≥42 day cutpoint for menstrual delay was based on the reports of Van Hooff et al [23,24] and Chiazze et al [18], and, in the current analysis sample, was found in 8% of reports of menstrual cycle length from age 14 to 19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A history of bilateral oophorectomy, which would result in a shortened reproductive period, and earlier menopause, have also been associated with less favorable glucose and insulin levels, 14,15 and increased risk of type 2 diabetes in some, 13,16 but not all, 12,1720 studies. Menstrual cycle characteristics such as length and regularity of menstrual cycle have also been associated with gestational diabetes and glucose intolerance in some, 2123 but not all, 13,24 studies.…”
Section: Introductionmentioning
confidence: 99%